Asserting the Female Mobility Pattern as Smart Mobility Indicator: Lesson Learned From Bus Rapid Transit (BRT) Passengers in Indonesia - Romadlon, Fauzan; Saintika, Yudha (Periodica Polytechnica Transportation Engineering, 2023)
Female passengers dominate the mobility by employing Bus Rapid Transit (BRT) in Indonesia and they possess a unique travel pattern compared to men. Women require more genuine investment efforts in comfortable and safer infrastructure for accessing and utilizing public transportation. The implementation of a smart city is one of the infrastructure investments. Smart mobility is one of the service cluster divisions, and smart mobility indicators are taken into account in the implementation. The objective of this study is to convert female mobility patterns and attitudes toward BRT service into smart mobility indicators. The method used is quantitative, and the questionnaire is designed to poll 209 people. Chi-Square and Likert scale are employed to analyze those criteria. The results demonstrate that the BRT has provided the female passenger services that they require at the current service level. The passenger pattern demonstrates that women depend on the BRT service to meet their transportation needs. Furthermore, the ICT criteria as a core for smart mobility has been challenging for both parties (female passengers and BRT operator). The limitation of this study is that it cannot demonstrate empirically that smart mobility is free gender biased and gaps until public transportation is fully inclusive.